Complete remission of advanced MSI-H rectal cancer in a young patient treated with nivolumab: a case report and critical appraisal of the literature - Liberko, Marian; Soumarova, Renata (Frontiers in Oncology, 2025)
Colorectal cancer is a heterogeneous disease, where therapy is chosen based on the presence or absence of predictive and prognostic markers, leading to a higher degree of treatment individualization with the aim of maximizing clinical benefit. In general, microsatellite-unstable tumors are characterized by high sensitivity to immunotherapy. A small percentage of patients with rectal cancer are diagnosed with microsatellite-unstable disease, and immunotherapy therefore represents a potentially curative option. We present a case report of a 34year-old patient with microsatellite-unstable locoregionally advanced rectal cancer who was treated with nivolumab monotherapy. The therapy led to a rapid response, with almost complete clinical remission of the primary tumor reported after only 3 months of therapy. After 6 months of nivolumab therapy, complete clinical remission of the disease was identified, and the patient is currently in a watch-and-wait mode as part of non-surgical management of the disease. The observed toxicity was consistent with the known toxicity profile of immunotherapy and did not lead to discontinuation of therapy. Our case report highlights the need to test for predictive markers in patients with locoregionally advanced rectal cancer in order to identify specific subtypes of the disease that can be treated with immunotherapy with a high probability of achieving clinical complete remission, thereby avoiding potentially risky surgery.